Antiproliferative and quinone reductase-inducing activities of withanolides derivatives - García, Manuela Emila (2014)
Two new and five known withanolides (jaborosalactones 2, 3, 4, 5, and 24) were isolated from the leaves of Jaborosa runcinata Lam. We also obtained some derivatives from jaborosalactone 5, which resulted to be the major isolated metabolite. The natural compounds as well as derivatives were evaluated for their antiproliferative activity and the induction of quinone reductase 1 (QR1; NQ01) activity. Structureeactivity relationships revealed valuable information on the pharmacophore of withanolide-type compounds. Three compounds of this series showed significantly higher antiproliferative activity than jaborosalactone 5. The effect of these compounds on the cell cycle was determined. Furthermore, the ability of major compounds to induce QR1 was evaluated. It was found that all the active test compounds are monofunctional inducers that interact with Keap1. The most promising derivatives prepared from jaborosalactone 5 include (23R)-4b,12b,21-trihydroxy-1,22-dioxo-12,23-cycloergostan-2,5,17,24-tetraen- 26,23-olide (18) and (23R)-21-acetoxy-12b-hydroxy-1,22-dioxo-12,23-cycloergostan-2,5,17,24-tetraen- 26,23-lactame (20).